Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1208/s12249-012-9828-x
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsion-Based Oxyresveratrol for Topical Treatment of Herpes Simplex Virus (HSV) Infection: Physicochemical Properties and Efficacy in Cutaneous HSV-1 Infection in Mice

Abstract: Abstract. The physicochemical properties of the optimized microemulsion and the permeating ability of oxyresveratrol in microemulsion were evaluated, and the efficacy of oxyresveratrol microemulsion in cutaneous herpes simplex virus type 1 (HSV-1) infection in mice was examined. The optimized microemulsion was composed of 10% w/w of isopropyl myristate, 35% w/w of Tween 80, 35% w/w of isopropyl alcohol, and 20% w/w of water. The mean particle diameter was 9.67±0.58 nm, and the solubility of oxyresveratrol in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 48 publications
4
26
0
Order By: Relevance
“…Similar effects of active substances on droplet size were reported previously when active substances were incorporated into colloidal systems, e.g. microemulsions (14), liposomes (10), nanosuspensions (15). The possibility of RES accumulation in the interfacial layer of nanostructure systems has been discussed earlier (6).…”
Section: Resultssupporting
confidence: 76%
“…Similar effects of active substances on droplet size were reported previously when active substances were incorporated into colloidal systems, e.g. microemulsions (14), liposomes (10), nanosuspensions (15). The possibility of RES accumulation in the interfacial layer of nanostructure systems has been discussed earlier (6).…”
Section: Resultssupporting
confidence: 76%
“…In this study, the ointment (lanovaseline) vehicle was better to solubilize the extract (2 %), and oral administration has not been performed by the low solubility in vehicles with low toxicity such as water and DMSO 1 %. Studies using oxyresveratrol derived from the traditional Thai plant, Artocarpus lakoocha Roxburgh, demonstrated that oxyresveratrol in cream base at 10 % applied three to five times daily (Lipipun et al 2011) and in oxyresveratrol microemulsion at 20-30 % w/w applied five times daily against HSV-1 for 7 days (Sasivimolphan et al 2012) were suitable for cutaneous HSV-1 mouse infection.…”
Section: Resultsmentioning
confidence: 99%
“…The values of polydispersity indices (PdI) were 0.21 ± 0.01, 0.26 ± 0.01, and 0.25 ± 0.00 for BME, ArtoME, and Arto + VcME, respectively. The values of PdI were low, which implied that the formulas had uniformity of the narrow size distribution (Sasivimolphan et al, 2012). The conductivity values of BME and ArtoME were 135.01 ± 0.22 and 160.32 ± 1.91 lS/cm, respectively.…”
Section: Physicochemical Properties Of Mesmentioning
confidence: 94%
“…Pseudo-ternary phase diagrams were constructed using the water titration method to obtain the suitable concentration range of components which formed microemulsion (Sasivimolphan et al, 2012). To investigate the area of ME region, surfactant were mixed with cosurfactant at a weight ratio (S mix ) of 1:1, 2:1, 3:1, and 4:1.…”
Section: Construction Of Pseudo-ternary Phase Diagramsmentioning
confidence: 99%
See 1 more Smart Citation